Presión mediática como factor incidente en la toma de decisiones de los operadores de justicia en procesos penales en el Cantón Ibarra. Análisis: Caso Zoé - Gudiño Lomas, Skarleth Nayeli (2025)
In the current Ecuadorian legal environment, media pressure has become an element of considerable relevance especially in criminal proceedings that arouse public interest. Hence, the general objective of the research was to analyze the impact of media pressure on criminal proceedings in the Ibarra-Ecuador canton, by studying the judicial actions in the Zoé Case and systematically reviewing local digital media, in order to determine whether rights were violated within the process. The study was developed under a qualitative approach with a dual level of depth (exploratory and descriptive), using the socio-legal, normative and analytical-synthetic methods. The techniques used were documentary review and structured interviews, the latter applied to a social communicator and judges of the Imbabura Criminal Guarantees Court based in the Ibarra canton, which allowed a comprehensive understanding of the phenomenon analyzed. The results show that, although the doctrine considers that media influence is a determining factor in judicial decisions in a procedure, the justice operators in charge of the Zoé Case applied objectivity and impartiality in the judicial ruling, respecting the guarantees of due process and protecting the rights of all parties involved. This study underlines the importance of having a justice system that preserves impartiality, moving away from external pressures and strictly complying with current regulations framed in constitutional principles.